2017
DOI: 10.1093/ofid/ofx163.432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Risk Category Predictions of Framingham Risk Score (FRS), Atherosclerotic Cardiovascular Disease Risk Score (ASCVD), Systematic Coronary Risk Evaluation (SCORE) and Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) in HIV Infected Patients

Abstract: Background Cardiovascular disease (CVD) is a major cause of mortality in HIV infected patients. Agreement between commonly used risk prediction equations for classification of high-risk individuals is varied in different populations. We aimed to compare the degree of agreement of four CVD risk calculators in a multicenter cohort.Methods A cross-sectional study was conducted among adult HIV patients who are followed in five tertiary centers between July 2016 and February 2017. Inclusion criteria were: age 40–74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 31 , 37 Some studies have assessed agreement/concordance in HIV-infected populations mainly using Cohen’s kappa. 40–42 In the general population for the three studies that assessed concordance using Lin’s concordance correlation coefficient, the values ranged from 0.44–0.51, which is moderate concordance. On the other hand the studies that used kappa statistic, the range of values was 0.22 (fair agreement)–0.78 (substantial agreement).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 , 37 Some studies have assessed agreement/concordance in HIV-infected populations mainly using Cohen’s kappa. 40–42 In the general population for the three studies that assessed concordance using Lin’s concordance correlation coefficient, the values ranged from 0.44–0.51, which is moderate concordance. On the other hand the studies that used kappa statistic, the range of values was 0.22 (fair agreement)–0.78 (substantial agreement).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the studies that used kappa statistic, the range of values was 0.22 (fair agreement)–0.78 (substantial agreement). In the HIV-infected populations, two studies 40 , 41 used kappa to test agreement between FRS and ASCVD algorithms with values of 0.61 and 0.75 falling in the substantial agreement category. The other study 42 used prevalence bias adjusted kappa (PABAK) and found no statistical difference in risk scores between tools.…”
Section: Discussionmentioning
confidence: 99%
“…22 Current reimbursement regulations for the prescription of lipid-lowering agents require a diagnosis of very high LDL cholesterol levels, which may create hesitancy among Turkish ID physicians to prescribe statins. 22,23 Similarly, the clinicians in our study did not seem to consider this comorbidity critical for ART selection. Except for cotrimoxazole prophylaxis, the presence of comedication was not shown to be a significant independent variable associated with concordance or absolute concordance in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 63%
“…22 Current reimbursement regulations for the prescription of lipid-lowering agents require a diagnosis of very high LDL cholesterol levels, which may create hesitancy among Turkish ID physicians to prescribe statins. 22,23 Similarly, the clinicians in our study did not seem to consider this comorbidity critical for ART selection.…”
Section: Discussionmentioning
confidence: 63%